Investigating the enforced disappearances of Algeria's 'Dark Decade': Omar D's and Kamel Khélif's commemorative art projects. Issue 2 (14th March 2016) - Howell, Jennifer
ABSTRACT: Some estimates indicate that as many as 7000 people have been reported missing in Algeria since 1992. While Islamists are responsible for some of these abductions, the majority can be attributed to the Algerian state. Human rights organisations have since called for the investigation of 'enforced disappearances' or the denial of individual freedoms in the form of state-sanctioned abductions, detentions, or executions. To put pressure on a government favourable to national reconciliation and the concealment of collective trauma, women continue to gather in front of the capital's administrative offices with photos of their missing so as to demand the identification of bodies and the restitution of memory. Yet, to state officials, the recurrence of this symbolic, pacifist act constitutes a threat to the Algerian republic, as it attempts to re-emerge unscathed from the ashes of a civil war without confronting its tumultuous past. Aware of the dangers inherent to such policies, Omar D (photographer) and Kamel Khélif (graphic artist) have joined the women's plight deploying similar arms. Their work re-appropriates identity photos of the missing and engages in the struggle against amnesia and the pursuit of justice. This article analyses the significance and impact of commemorative art practices that use identity photographs to liberate the word, to denounce mass disappearances and the effacement of a new democratic Algerian identity. For artists and families, identity photographs surface as a powerful political space where individual memories become collective and where citizens can hold the state accountable for its actions.